Healthy aging and chronic kidney disease - Reshma Aziz Merchant; Anantharaman Vathsala (The Korean Society of Nephrology, 2022)
The world population is aging and the prevalence of noncommunicable diseases such as chronic kidney disease (CKD) will increase significantly. With advances in medical treatment and public health, the human lifespan continues to outpace the health span and the last decade of life is generally spent in poor health. In 2015, the World Health Organization defined healthy aging as 'the process of developing and maintaining the functional ability that enables wellbeing in older age.' CKD is increasingly being recognized as a model of accelerated aging and is associated with physical performance decline, cognitive decline, falls and fractures, poor quality of life, loss of appetite, and inflammation. Frailty and dementia are the final pathways and key determinants of disability and mortality independent of underlying disease. CKD, dementia, and frailty share a triangular relationship with synergistic actions and have common risk factors wherein CKD accelerates frailty and dementia through mechanisms such as uremic toxicity, metabolic acidosis and derangements, anorexia and malnutrition, dialysis-related hemodynamic instability, and sleep disturbance. Frailty accelerates glomerular filtration decline as well as dialysis induction in CKD and more than doubles the mortality risk. Anorexia is one of the major causes of protein-energy malnutrition, which is also prevalent in the aging population and warrants screening. Healthcare systems across the world need to have a system in place for the prevention of CKD amongst high-risk older adults, focusing on screening for poor prognostic factors amongst patients with CKD such as frailty, poor appetite, and cognitive impairment and providing necessary person-centered interventions to reverse underlying factors that may contribute to poor outcomes.